2018
DOI: 10.1021/acsbiomaterials.8b00678
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Amphiphilic Miktoarm Star Copolymers for Anticancer Drug Delivery

Abstract: The preparation of various types of miktoarm star polymers with precisely controlled structures (A2B, ABC, AB2C2, etc.) has made significant progress due to the considerable advances in the synthetic strategies, including multistep protections/deprotections, orthogonality, and integration of different polymerization techniques. However, compared to the well-developed synthesis methodologies, the investigations on miktoarm star copolymers as drug delivery vehicles remain relatively unexplored, especially for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 40 publications
0
30
0
Order By: Relevance
“…The miktoarm polymers were found to have no significant cytotoxicities, could be self-assembled into micelles, and were able to efficiently encapsulate and deliver doxorubicin (DOX) to cells. Interestingly, the most hydrophobic PCL 3 POEGMA derived micelles had the lowest CMC, the highest DOX encapsulation efficiency, and the best therapeutic efficiency for DOX release [ 70 ].…”
Section: Synthetic Approaches To Miktoarm Star Polymersmentioning
confidence: 99%
See 2 more Smart Citations
“…The miktoarm polymers were found to have no significant cytotoxicities, could be self-assembled into micelles, and were able to efficiently encapsulate and deliver doxorubicin (DOX) to cells. Interestingly, the most hydrophobic PCL 3 POEGMA derived micelles had the lowest CMC, the highest DOX encapsulation efficiency, and the best therapeutic efficiency for DOX release [ 70 ].…”
Section: Synthetic Approaches To Miktoarm Star Polymersmentioning
confidence: 99%
“…Rather than strictly increasing hydrophobic block sizes, one study attempted to change the ratio of hydrophilic and hydrophobic segments through four different A 2 B, A 2 B 2 , AB 3 , and A 3 B (A = PCL, B = POEGMA) miktoarm star polymers [ 70 ]. It was found that increasing the number of PCL arms to POEGMA resulted in the largest increase in micelle stability, with a minimum CMC of 2.66 mg/L for the A 3 B miktoarm star.…”
Section: Amphiphilic Miktoarm Star Polymers: Self-assemblymentioning
confidence: 99%
See 1 more Smart Citation
“…The miktoarm-block copolymers demonstrate exclusive phase-separation behavior either in solution or in bulk compared with linear-block copolymers due to the organization of the polymers, in which two constructional blocks are connected to a distinct confluence point [ 8 , 9 , 10 , 11 ]. This ability imparts miktoarm-block copolymers with wide potentials for use as nanocarriers of drugs compared with corresponding linear-block copolymers [ 12 , 13 , 14 , 15 , 16 ]. The synthesis of AB 2 miktoarm-block copolymers is mostly practicable with a classification of different polymerization methods.…”
Section: Introductionmentioning
confidence: 99%
“…Many examples of this strategy exist in the context of cancer therapy. [29][30][31][32] Aside from the unique inherent properties of star polymers, a stimuli-responsive character can be embedded in them as well. Various stimuli such as light, 33 pH (used in our previous work) 14 and heat 34 can be used (and combined 35 ) as triggers to induce a specific response from the star polymer.…”
Section: Introductionmentioning
confidence: 99%